Characterization of Mycobacterium marinum infections in zebrafish wounds and sinus tracts. Issue 3 (10th July 2017) - Chen, Ling; Liu, Zhen; Su, Yingjun; Wang, Di; Yin, Bin; Shu, Bin; Zhang, Jishen; Zhu, Xiaoyan; Jia, Chiyu
Abstract: The impaired healing of Mycobacterium tuberculosis –infected wounds is a clinical challenge, and the mechanisms involved are still not clear. The zebrafish model of Mycobacterium marinum infection has provided surprising insights into the pathogenesis of tuberculosis in humans. Similarly, the major principles and phases of cutaneous wound healing are conserved among adult mammals and adult zebrafish. Here, we injected Mycobacterium marinum into the dorsal muscles of adult zebrafish and observed the development of chronic wound pathology. Deep sequencing showed that gene expression related to muscles was down‐regulated, whereas expressions of the IL‐1β, TNF‐α, dram1 genes and the transcript of mir1‐2 gene were up‐regulated in infected wounds of zebrafish compared with control zebrafish. Muscles are immune‐responsive tissues. Thus, muscles may play a role in the anti– Mycobacterium tuberculosis immunologic process, which leads to apoptosis of the infected muscle cell and formation of the subcutaneous sinus tract.